2019
DOI: 10.1021/acsami.9b07318
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering to Eliminate Hysteresis of Carbon-Based Planar Heterojunction Perovskite Solar Cells via CuSCN Incorporation

Abstract: A carbon electrode with low cost and high stability exhibited competitiveness for its practical application in organic–inorganic hybrid perovskite solar cells (PSCs). Nonetheless, issues such as poor interface contact with an adjacent perovskite layer and obvious hysteresis phenomenon are bottlenecks that need to be overcome to make carbon-based PSCs (C-PSCs) more attractive in practice. Herein, we report an effective method to enhance the interfacial charge transport of C-PSCs by introducing the CuSCN materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 53 publications
3
54
0
Order By: Relevance
“…This difference is attributed to the presence of shallow trap states at the interfaces of the perovskite/charge selective layer interface. [40] The loss of electron generated by the weaker monochromatic light used in the EQE measurement at the perovskite/charge selective contact interface becomes severe as a consequence of the trapping process, while these trap states can be filled up under high illumination intensity as in the case of the J-V measurement, leading to the mismatch between two measurements. [41] To gain a deeper insight into the effect of the HTL on the charge (ions, electrons, and holes) transport and accumulation at the interfaces, we probed the fabricated PSCs by EIS.…”
Section: Resultsmentioning
confidence: 99%
“…This difference is attributed to the presence of shallow trap states at the interfaces of the perovskite/charge selective layer interface. [40] The loss of electron generated by the weaker monochromatic light used in the EQE measurement at the perovskite/charge selective contact interface becomes severe as a consequence of the trapping process, while these trap states can be filled up under high illumination intensity as in the case of the J-V measurement, leading to the mismatch between two measurements. [41] To gain a deeper insight into the effect of the HTL on the charge (ions, electrons, and holes) transport and accumulation at the interfaces, we probed the fabricated PSCs by EIS.…”
Section: Resultsmentioning
confidence: 99%
“…[157] The presence of the ion diffusion often leads to hysteresis and unstable overall conversion efficiencies during the I-V measurement. [41,[158][159][160][161][162][163][164][165][166] The ion transports in halide perovskite materials is contributed by the point and extended defects (intrinsic). In addition, extrinsic factors such as light, heat, and electrical fields accelerate the ion transports.…”
Section: Ion Diffusion In Halide Perovskitementioning
confidence: 99%
“…It should be noted that no white light bias was exerted on the devices during EQE measurements to avoid the trap filling effect. 53 It was found that the gradient-cooled device exhibited larger EQE values compared to the quenched device, and the statistical distribution of EQE values at three typical wavelengths (400 nm, 500 nm, and 600 nm, Fig. S8, ESI †) demonstrated the reproducibility of this result.…”
Section: Esi †) a Close Comparison Of Photovoltaic Parametersmentioning
confidence: 72%